Pemanfaatan Artificial Intelligence Dalam Pengembangan Sdm Unggul Di UMKM Kecamatan Gunung Sindur - Syafi’i, Imam; Wachidin, Muhammad Soffan; Sunarsi, Denok; Susanto, Hengli; Utami, Monika Agustia; Irmawanti, Irmawanti; Rusilowati, Umi (LPPM STIE Hidayatullah Depok, 2025)
Seminar pelatihan dengan tema